(untitled) (Research Nepal Journal of Development Studies, 2024)
This paper presents a comparative analysis of land reforms in Cuba, China, and Vietnam through the lens of Marxist agrarian theory. Utilizing a comparative historical methodology, this library based study conducts a qualitative documentary analysis of secondary sources, including government reports and academic literature, triangulated with quantitative data on agricultural output. This approach facilitates a systematic examination of how core Marxist principles—such as the abolition of feudal-capitalist structures, collectivization, and wealth redistribution—were adapted to distinct national contexts to empower rural populations and achieve socio-economic justice. The analysis reveals that while all three cases successfully established a foundation for poverty reduction, food security, and economic sovereignty by dismantling historical inequities, their long-term efficacy was contingent on pragmatic adaptations. China’s “Post-collectivization Household Responsibility System” and Vietnam’s market-oriented “Doi Moi” reforms catalyzed unprecedented growth, though often at socio-environmental cost. Conversely, Cuba’s agroecological focus ensured food security despite constraints. The study concludes that sustainable agrarian transformation requires moving beyond rigid ideological models. Instead, it necessitates a hybrid governance framework that strategically get hitched Marxist concerns for equity with market mechanisms for efficiency. This is best achieved by ensuring secure, transferable land-use rights for smallholders, providing targeted state support, and integrating environmental stewardship and agroecological practices from the outset to ensure both productive and equitable outcomes.